Light sterile neutrino sensitivity of 163Ho experiments - Gastaldo, Loredana; Giunti, Carlo; Zavanin, Eduardo Marcio (Journal of high energy physics, 2016)
We explore the sensitivity of $^{163}$Ho electron capture experiments to neutrino masses in the standard framework of three-neutrino mixing and in the framework of 3+1 neutrino mixing with a sterile neutrino which mixes with the three standard active neutrinos, as indicated by the anomalies found in short-baseline neutrino oscillations experiments. We calculate the sensitivity to neutrino masses and mixing for different values of the energy resolution of the detectors, of the unresolved pileup fraction and of the total statistics of events, considering the expected values of these parameters in the two planned stages of the ECHo project (ECHo-1k and ECHo-1M). We show that an extension of the ECHo-1M experiment with the possibility to collect $10^{16}$ events will be competitive with the KATRIN experiment. This statistics will allow to explore part of the 3+1 mixing parameter space indicated by the global analysis of short-baseline neutrino oscillation experiments. In order to cover all the allowed region, a statistics of about $10^{17}$ events will be needed.
Im Titel ist die Zahl "163" hochgestellt
Gesehen am 13.05.2020